Tetraparese spastik akibat schwannoma servikal: sebuah laporan kasus - Rizaldy Taslim Pinzon; Gusti Agung Sinta Shakuntala; Vanessa Veronica (Intisari Sains Medis, 2022)
Introduction: Schwannoma is a benign nerve sheath tumor that occurs more frequently in the peripheral nervous system than in the central nervous system. Spinal schwannomas are most frequently found in the thoracic or lumbar regions but are uncommon in the cervical region. This paper describes a cervical schwannoma that is associated with spastic tetraparesis. Case Presentation: A 50-year-old man presented with the primary complaint of having difficulty moving his upper and lower limbs. The patient is fully conscious and has a temperature of 36.2°C, a respiratory rate of 22 breaths per minute, and a pulse rate of 108 beats per minute. Neurological evaluation revealed bilaterally diminished strength in the superior and inferior extremities. Cervical magnetic resonance imaging (MRI) with and without contrast revealed a grade 2 hernia nucleus pulposus (HNP) and an extramedullary-intradural mass in the anterior cervical vertebral canal region between C5 and C7, compressing and obliterating the cerebrospinal fluid spaces. A laminectomy was performed, and an intradural tumor mass in the C5-C7 region was obtained. Conclusion: Schwannomas, although rare, can cause spastic tetraparesis if they compress the cervical spinal cord.   Latar Belakang: Schwannoma adalah tumor selubung saraf jinak yang lebih sering terjadi di luar sistem saraf pusat. Schwannoma spinal dapat terjadi di regio thorakal atau lumbar, namun jarang terjadi pada regio servikal. Studi ini melaporkan schwannoma servikal yang menyebabkan tetraparese spastik. Presentasi Kasus: Seorang laki-laki umur 50 tahun datang dengan keluhan utama kedua anggota gerak atas dan bawah sulit digerakkan. Pasien sadar penuh dengan suhu 36,2°C, laju respirasi 22 kali per menit, nadi 108 kali per menit. Pemeriksaan neurologis menunjukkan adanya penurunan kekuatan ekstremitas superior dan ekstremitas inferior bilateral. Magnetic resonance imaging (MRI) servikal dengan kontras dan tanpa kontras menunjukkan hernia nucleus pulposus (HNP) grade 2 dan massa ekstramedular-intradural pada regio kanalis vertebra servical anterior setinggi C5-C7 yang menyebabkan kompresi dan obliterasi ruang cairan serebrospinal. Dilakukan laminektomi dan didapatkan massa tumor intradural C5-C7. Kesimpulan: Schwannoma, walaupun jarang, dapat menyebabkan tetraparese spastik jika menekan medula spinalis servikal.